2010
DOI: 10.4061/2010/281692
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease, Single Nucleotide Polymorphisms; and the Renin Angiotensin System: Is There a MicroRNA Connection?

Abstract: Essential hypertension is a complex disorder, caused by the interplay between many genetic variants, gene-gene interactions, and environmental factors. Given that the renin-angiotensin system (RAS) plays an important role in blood pressure (BP) control, cardiovascular regulation, and cardiovascular remodeling, special attention has been devoted to the investigation of single-nucleotide polymorphisms (SNP) harbored in RAS genes that may be associated with hypertension and cardiovascular disease. MicroRNAs (miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 120 publications
(152 reference statements)
0
13
0
Order By: Relevance
“…[52][53][54][55][56][57][58][59][60] In the kidney, miRs have been linked to diabetic nephropathy, polycystic kidney disease, renal cancer, AKI, transplant rejection, and kidney development. 59,[61][62][63][64][65][66] Recently, several studies have focused on the role of miR-192, an miR known to be expressed in the kidney cortex, in the profibrotic progression of nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54][55][56][57][58][59][60] In the kidney, miRs have been linked to diabetic nephropathy, polycystic kidney disease, renal cancer, AKI, transplant rejection, and kidney development. 59,[61][62][63][64][65][66] Recently, several studies have focused on the role of miR-192, an miR known to be expressed in the kidney cortex, in the profibrotic progression of nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments involving transfection of cells that mimic mature miR-155 showed that this miR inhibited the expression of human AT1 receptor and also attenuated Ang II-induced signaling via the AT1 receptor in fibroblasts and VSMCs. Other experiments with antimir have demonstrated that transfection of anti-miR-155 increased AT1 receptor expression and also enhanced Ang II signaling via this receptor (60). Despite the fact that the literature has presented studies discussing the relationship of miRs and cardiac hypertrophy in cardiovascular disease and phenotypes, it is important to emphasize that, to our knowledge, only one study involving cardiac hypertrophy induced by physical training and miRs has been published, and the differential expression between the types of cardiac hypertrophy (physiological vs pathological) has not been explored.…”
Section: Micrornas Can Be Tiny Modulators Of Cardiac Hypertrophy Indumentioning
confidence: 99%
“…It has been found that SNPs could affect the protein structure, changing their amino-acid sequence or interfering with their regulation (5). Three different SNPs (rs11640851, rs8052394 and rs1610216) in MT genes were shown to be associated with diabetes and its complications (8,6,22).…”
Section: Introductionmentioning
confidence: 99%